Use of paddy husk compost on improving ammonium and nitrate - Ellferaellia Jonius,
Incubation studies were conducted for 30 days, 60 days and 90 days respectively to determine the effects of urea and rice husk composts to control the loss of NH4 and NO from urea. The compost is produced from paddy husk compost that used to improve the efficiency of Nby absorbing ammonium ions from urea and releasing it on the plant to be used by the plant because the compost of rice husk has a high appeal to the ammonium ions.